(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
• This paper presents internalization of Character Values in Social Science Learning Based on Local Wisdom in Elementary Schools in Lampung, Indonesia. The purpose of this research is to understand the comprehension of character values in local wisdom-based social science learning, and to explore strategies to strengthen character values in local wisdom-based social science learning. This study employs a qualitative-naturalistic method with an ethnographic approach to understand the internalization of character values in social science learning at elementary schools in Metro City, Lampung. It involves participatory observation, interviews, and curriculum document analysis. Local wisdom-based social science learning in Lampung community can shape the behavior and social personality of students, but it requires comprehensive planning and evaluation. The focus on social science learning in elementary schools in Metro City, Lampung limits the generalizability of the findings to other educational contexts, compounded by time and resource constraints that may impact the broader generalization of this research. There is a need for the development of a local wisdom-based approach to social science learning in elementary schools, with the integration of Piil Pesenggiri values as a part of character values integration.